KAJIAN KERUSAKAN EKOSISTEM HUTAN MANGROVE AKIBAT AKTIVITAS MANUSIA DALAM RANGKA PELESTARIAN LINGKUNGAN (KASUS DI PANTAI POLEWALI MANDAR PROVINSI SULAWESI BARAT) - Carong, SUPARJO RAZASLI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
These last few years, the mangrove forest ecosystem had been targeted to be used as a wide range of activities by human, either directly or indirectly. Data of Polewali Mandar regency show that mangrove forests have been partially damage so that their numbers begin to decrease and some mangrove forests area converted as cultivation are namely pond. The purpose of this study is to identify the types of mangrove forest damage due to human activities of Polewali Mandar, to assess the level of damage of mangrove forest ecosystems, and to formulate environmental management strategies due to damage of mangrove forest ecosystems fot the environmental conservation of Polewali Mandar regency. The research was conducted throughout the month of May 2014 in Mampie Shore, Wonomulyo District, Polewali Mandar Regency. Social data collection conducted in-depth interview using a structured question guide, while mangrove forest vegetation data collection using proportionate random sampling technique. The results showed that there are 3 types of damage namely abiotic components damage (high levels of coastal erosion and disruption of tidal phase), biotic components damage (mangrove diversity is sparse, and the lack of regeneration from mangrove forest vegetation), and cultural components damage (conversion of mangrove forests into farms, logging for domestic use, and settlement activities). Medium-damage level are found at B, C, E, F, G, H, and I block (range value 20-26). While low-damage level are found A, D, and E block. Management strategy of mangrove forests at Mampie shore based on the SWOT analysis are to make Mampie remaining mangrove forests into ecotourism, improving the quality of human resource (local community) and knowledge in the utilization of mangrove forests for economic, priority handling mid-damage level of mangrove forest by the local government, the planting of mangrove seedling in the pond area (silvofishery development), planting mangroves in the abration area with stakes, improved rhydrological flow of Mampie so that sdistribution mangrove normally, and rehabilitation of mangrove forest including the medium-damage level.